2020
DOI: 10.1093/eurheartj/ehaa764
|View full text |Cite
|
Sign up to set email alerts
|

Is metoprolol more cardioprotective than other beta-blockers?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Previous animal study demonstrated that only metoprolol, but not atenolol or propranolol, reduced infarct size and inflammation a rat model of MI 28 . Furthermore, beta-blockers which exert ancillary cardioprotective properties such as carvedilol through alpha 1-adrenoceptor blockade and antineutrophil and antioxidative actions, or nebivolol which enhances nitric oxide signalling may have additional benefit on cardioprotection 29 . Importantly, the interference of co-morbidities and co-medications with cardioprotection has been established 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal study demonstrated that only metoprolol, but not atenolol or propranolol, reduced infarct size and inflammation a rat model of MI 28 . Furthermore, beta-blockers which exert ancillary cardioprotective properties such as carvedilol through alpha 1-adrenoceptor blockade and antineutrophil and antioxidative actions, or nebivolol which enhances nitric oxide signalling may have additional benefit on cardioprotection 29 . Importantly, the interference of co-morbidities and co-medications with cardioprotection has been established 30 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a wealth of preclinical data on IS reduction by β -blockers in animal studies of I/R, although, as noted later, none have been successfully and reproducibly translated to humans. Studies in pigs have shown MRI-based evidence for cardioprotection by metoprolol ( Ibanez et al, 2007 ; Ibanez et al, 2011 ; García-Ruiz et al, 2016 ; Heusch and Kleinbongard, 2020 ; Lobo-Gonzalez et al, 2020 ), and histology-based evidence for cardioprotection by carvedilol ( Bril et al, 1992 ; Feuerstein and Ruffolo, 1995 ), atenolol, and the short-acting β -blocker landiolol ( Park et al, 2011 ). Carvedilol also reduced the area of no-reflow in pigs following I/R, assessed by myocardial contrast echocardiography ( Zhao et al, 2008 ).…”
Section: Effects Of Pharmacological Treatment Of Comorbidities On Car...mentioning
confidence: 99%
“…Myocardial protective drugs, such as cardiotonic agents, β-blockers, , and antiinflammatory drugs, are conducive to improving cardiac function and reducing the infarct size. However, most pharmaceuticals lack specificity to the heart, which limits their bioavailability at the lesion area.…”
Section: Introductionmentioning
confidence: 99%
“…11 Therefore, in order to protect the jeopardized patients, it is vital to save the I/R heart in time before spiral deterioration takes place, so as to avoid irreversible damage and structural destruction. 12 Myocardial protective drugs, such as cardiotonic agents, 13 βblockers, 14,15 and antiinflammatory drugs, 16 are conducive to improving cardiac function and reducing the infarct size. However, most pharmaceuticals lack specificity to the heart, which limits their bioavailability at the lesion area.…”
Section: ■ Introductionmentioning
confidence: 99%